(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the issues of the public administration system in the Kyrgyz Republic, as well as a comparative analysis with neighboring countries in the context of sovereignty in accordance with the Constitution of the Kyrgyz Republic dated May 5, 2021. Frequent change of heads of the branch of power in the country. The number of deputies of the Zhogorku Kenesh of the Kyrgyz Republic from 1991 to 2021 is disclosed. The status of the People’s Kurultai and the main directions, goals, objectives and expected results of the Doctrine of the Kyrgyz Republic “National Spirit-World Heights” (Kyrgyz Republic «Uluttuk dem-duynoluk biyiktik», ungu zhol) with brief conclusions.